Factors related to failure to attend the consultation to receive the results of the Pap smear test - Camila Teixeira Moreira Vasconcelos; Denise de Fátima Fernandes Cunha; Cássia Fernandes Coelho; Ana Karina Bezerra Pinheiro; Namie Okino Sawada (Universidade de São Paulo, 2014)
OBJECTIVE: to identify the factors related to the failure of women to attend the follow-up consultation to receive the results of the Pap smear test.METHOD: a cross-sectional study, carried out with 775 patients who underwent the Pap smear test in the Centro de Saúde da Família of Fortaleza, between September 2010 and February 2011.RESULTS: the majority of the women studied were young (≤35 years), had low levels of education (≤7 years of study), and commenced sexual activity early (≤20 years), with 17.0% of them failing to return to receive the test results. Statistically significant results for the failure to return were related to: young women (p=0.001); early onset of sexual activity (p=0.047); and inadequate knowledge about the Pap smear test (p=0.029). Conclusion the fact that the women failed to return for the result is a problem for the control of cervical cancer and must be addressed through educational strategies that reinforce the importance of the return for the early detection of this cancer.